2018
DOI: 10.1140/epjc/s10052-018-5602-x
|View full text |Cite
|
Sign up to set email alerts
|

Joule–Thomson expansion of Kerr–AdS black holes

Abstract: In this paper, we study Joule-Thomson expansion for Kerr-AdS black holes in the extended phase space. A Joule-Thomson expansion formula of Kerr-AdS black holes is derived. We investigate both isenthalpic and numerical inversion curves in the T -P plane and demonstrate the cooling-heating regions for Kerr-AdS black holes. We also calculate the ratio between minimum inversion and critical temperatures for Kerr-AdS black holes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
97
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 59 publications
23
97
1
Order By: Relevance
“…We have observed that for the case of linear axions, when they possess standard kinetic term, the inversion curve possesses only one branch, similar to what was obtained in [32][33][34][35][36][37], behavior that differs from the case of Van der Wall fluids. The net effect of the momentum relaxation mechanism, which is controlled by our coupling β, is that the inversion curve is enlarged for higher values of β.…”
Section: Final Commentssupporting
confidence: 75%
See 3 more Smart Citations
“…We have observed that for the case of linear axions, when they possess standard kinetic term, the inversion curve possesses only one branch, similar to what was obtained in [32][33][34][35][36][37], behavior that differs from the case of Van der Wall fluids. The net effect of the momentum relaxation mechanism, which is controlled by our coupling β, is that the inversion curve is enlarged for higher values of β.…”
Section: Final Commentssupporting
confidence: 75%
“…Furthermore, we study the isenthalpic curves for c 1 = −1 and These observations are novel in the following aspects. Comparing with previous works [32][33][34][35][36][37], where only one branch was obtained, we first obtain two branches for the inversion curve, which is similar to the Van der Waals fluids case. However, the minimal inversion temperature is negative unlike the case of Van der Waals fluids.…”
Section: A Planar Black Holes In Massive Gravitysupporting
confidence: 60%
See 2 more Smart Citations
“…The Joule-Thomson expansion for the charged AdS and Kerr-AdS black holes is considered in Refs. [38,39]. Studying the phase transitions of the black holes in the AdS spacetime is motivated by the gauge/gravity correspondence [40,41], where the black hole can be identified with an approximately thermal state in the dual strongly coupled field theory [42,43].…”
Section: Introductionmentioning
confidence: 99%